PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN PAK TERHADAP HASIL BELAJAR SISWA KELAS XI SMK NEGERI 1 LUMBAN JULU TOBA SAMOSIR TAHUN AJARAN 2017/2018 - Nurmala Rina Marpaung (IAKN Tarutung, 2018)
Abstract, This study aims to determine the effect of the use of learning media Christian Religious Education Against Student Results Class XI SMK Negeri 1 Lumbanjulu Toba Samosir Year Learning 2017/2018. Hypothesis of this research is There is Positive Influence and Significant Use of PAK Learning Media to Student Result of Class XI SMK Negeri 1 Lumbanjulu. This research is descriptive and inferential quantitative research. The population is all students of class XI SMK Negeri 1 Lumbanjulu which amounted to 113 and the sample research taken 30% of the entire population so that the sample research into 34 students. This study concludes that the learning media of Christian Religious Education have a positive and significant effect on student learning outcomes. The result of data analysis shows that there is a positive and significant effect of PAK Learning Media on Student Results of Grade XI SMK Negeri 1 Lumban Julu with coefficient of determination (r2) = 12,71% and significant test of influence obtained Fhitung Ftabel equal to 2,1585 2.042, meaning H0 is rejected and Ha accepted. In connection with the results of this study, the authors suggest for teachers of Christian Religious Education to increase the use and utilization of instructional media in accordance with the material in order to assist students in improving learning outcomes. Keywords : Use of PAK Learning Media, Student Learning Outcomes